Zondervan 2018 church and nonprofit tax and financial guide : for 2017 tax returns - Busby, Dan; Laue, Vonna; Van Drunen, John; Martin, J. Michael, 1941-; Recorded Books, Inc. (Grand Rapids : Zondervan, 2018)
The Zondervan 2018 Church and Nonprofit Tax and Financial Guide annual reference guide continues to be one of the few resources offering tax and financial advice to churches and nonprofit organizations. Issues of financial accountability, receiving and maintaining tax-exempt status, accounting for charitable gifts, and other crucial topics receive careful and full discussion. The 2018 edition also contains a thorough description of tax laws affecting churches and other nonprofit organizations, ensuring compliance with all regulations. The book includes expert advice on handling charitable gifts, sample policies and procedures, easy techniques for simplifying financial policies and procedures, insights on medical expense reimbursements, key steps in sound compensation planning, and examples of required IRS filings.
Includes bibliographical references and indexes.
Keywords: Nonprofit organizations -- Taxation -- Law and legislation -- United States; Corporations, Religious -- Taxation -- Law and legislation -- United States; Church property -- Taxation -- United States; RELIGION / Christian Ministry / Pastoral Resources; Church property -- Taxation; Corporations, Religious -- Taxation -- Law and legislation; Nonprofit organizations -- Taxation -- Law and legislation; United States